Progress in Vaccination of Prophylactic Human Papillomavirus Vaccine - Zhou, Xu; Sun, Lihua; Yao, Xiaoxiao; Li, Guangquan; Wang, Yicun; Lin, Yang (Frontiers in Immunology, 2020)
The human papillomavirus (HPV) vaccine plays an important role in preventing a series of diseases caused by HPV. Recent studies have shown that as a primary prevention measure, it can considerably prevent HPV infection and HPV-associated cervical cancer. However, studies on the safety, efficacy, and coverage of the HPV vaccine remain insufficient, especially in developing countries. Therefore, in this review, we outlined the recent studies of the HPV vaccine in terms of immunogenicity, safety, efficacy, latest vaccination concepts, and strategies. This review may provide a theoretical basis for use of the HPV vaccine.